Role of macrophage scavenger receptors in atherosclerosis - Kzhyshkowska, Julia; Neyen, Claudine; Gordon, Siamon (Immunobiology, 2012)
Accumulating evidence indicates that atherosclerosis is a chronic inflammatory disease. The key innate immune cells that are involved in the pathogenesis of atherosclerosis are circulating monocytes and plaque macrophages. Complex interplay between immune and metabolic processes results in pathological activity of these cells. The best understood pathological process mediated by macrophages is their inability to process modified lipoproteins properly resulting in the formation of foamy cells, which are a dangerous component of atherosclerotic plaques. Key molecules involved in the recognition and processing of modified lipoproteins are scavenger receptors (SR). This is a large family of surface expressed structurally heterogeneous receptors with a broad spectrum of endogenous and exogenous ligands. The common functional feature of SR is internalisation of extracellular components and targeting them for lysosomal degradation. However, these relatively simple functions can have complex consequences, since they are linked to diverse specific signalling pathways and to other membrane transport pathways. Moreover, scavenger receptors can co-operate with other types of receptors increasing the variability of the macrophage response to multiple extracellular ligands. At least some SRs respond to modified lipoproteins by amplification of inflammation and accumulation of macrophages in the plaque, while some SRs may support tolerogenic reactions. Outcome of different SR activities will be the decision of monocytes and macrophage to guard homeostatic balance, support atherosclerosis progression and plaque instability by inflammatory reactions, or support rapid fibrotic processes in the plaque that stabilise it. Despite the accumulating knowledge about the molecular mechanisms of scavenger receptor action, their role in the progression of atherosclerosis remains controversial. The activities of scavenger receptors that can contribute to each of these processes are a subject of current review.
Gesehen am 30.10.2018